Muslim Digital Identities in Indonesia and Thailand: Social Media, Authority, and Cultural Belonging - Kheryadi, Kheryadi; Chorbwhan, Rungroj (Digital Muslim Review, 2025)
This study examines the role of social media in shaping Muslim identities in Indonesia and Thailand, highlighting how national contexts mediate digital religious practices. Drawing on digital ethnography, surveys, and interviews, the research shows that online platforms function as key arenas where Muslims negotiate faith, authority, and identity. In Indonesia, a Muslim-majority society, social media is often intertwined with politics: it amplifies religious movements, mobilizes mass campaigns such as the 212 Action, and empowers digital preachers who redefine religious authority. Platforms like Instagram, YouTube, and TikTok shape public perceptions of piety by blending Islamic values with popular culture and commercial interests. In contrast, Thai Muslims—situated as a minority within a Buddhist-majority society—use digital platforms more subtly for cultural preservation, solidarity, and resistance against marginalisation. Online spaces enable them to assert belonging, challenge stereotypes, and sustain religious life otherwise constrained offline. Across both contexts, social media emerges not only as a medium of expression but also as a site of tension, fragmentation, and negotiation, underscoring its transformative power in the construction of Muslim digital identities in Southeast Asia.